Photoelectrical parameters of ncds-pcdte thin film solar cells with CDO buffer layer - Gaşin, Petru (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2016)
The results of the studies of the effect of a CdO buffer layer on the photoelectrical parameters of CdS–CdTe solar cells have been described. It has been found that the formation of a 5–8 nm thick CdO buffer layer leads to an increase in the CdS–CdTe solar cell open circuit voltage (Voc) by 90–140 mV, short circuit current (Isc) by 1.4–3.2 mA/cm2, and efficiency by 2.8–4.1% at 300 K and an illumination of 100 mW/cm2.